Eficácia do avanço do músculo genioglosso comparado ao avanço maxilo-mandibular no tratamento da síndrome da apneia e hipopneia obstrutiva do sono : uma revisão sistemática com metanálise - Silva Junior, Djalma Carmo Da (2016)
The obstructive sleep apnea and hypopnea syndrome (OSAS) is characterized by repeated episodes of complete or partial interruption of the airflow as consequence of upper airway obstruction during sleep. Indications for the surgical treatment of OSAS, as well as the evidence on the efficacy and safety of the surgical techniques available merit further scientific scrutiny. Objective: To perform a systematic review on the efficacy of genioglossus advancement (GA) when compared to maxillomandibular advancement (MMA) for the treatment of patients with OSAS. Method: A systematic electronic search was conducted in the LILACS, PubMed and SciELO databases to identify studies involving patients undergoing MMA and GA for the treatment of OSAS. The guidelines presented by the PRISMA statement were followed. The eligible articles were subjectively evaluated regarding their methodological quality based on a checklist of the Critical Appraisal Skills Programme (CASP). A meta-analysis was carried out with the aid of RevMan. Results: The systematic literature search resulted in 889 records, of which 41 articles were examined for their content. After full text analysis, six studies were included in this review and allowed for inferences about the efficacy of surgical procedures at hand. Conclusion: GA showed lower treatment efficacy, as evidenced by the apnea-hypopnea index recorded by polysomnography. The results of the meta-analysis show that the MMA is superior to GA in the context of surgical treatments for OSAS.